EXPERIMENTIAL APPROACHES TO THE STEPS OF THEOFHILOS AND HOMER - Maria Manola; I Vekri (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2021)
This study traces the works of the great folk painter Theophilos Hadjimichael of Lesvos, guided by the lights of history, literature, tradition, art and culture, especially in those paintings which place their source of inspiration in the epic poetry of Homer. A story teller grandfather, a “magician”, who